2008
DOI: 10.1021/bm800246x
|View full text |Cite
|
Sign up to set email alerts
|

Facile, Efficient Approach to Accomplish Tunable Chemistries and Variable Biodistributions for Shell Cross-Linked Nanoparticles

Abstract: The in vivo behavior of shell cross-linked knedel-like (SCK) nanoparticles is shown to be tunable via a straightforward and versatile process that advances SCKs as attractive nanoscale carriers in the field of nanomedicine. Tuning of the pharmacokinetics was accomplished by grafting varied numbers of methoxy-terminated poly(ethylene glycol) (mPEG) chains to the amphiphilic block copolymer precursors, together with chelators for the radioactive tracer and therapeutic agent (64)Cu, followed by self-assembly into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
104
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 86 publications
(106 citation statements)
references
References 66 publications
2
104
0
Order By: Relevance
“…The quantification of the impact of mPEG grafting density on the surface of organic polymer nanoparticles was made through a series of rigorous experimental studies (4). The key to the synthesis of the nanoparticles with well-defined and variable levels of mPEG surface grafts was the incorporation of the mPEGs onto the backbone of polymer building blocks that were designed to then undergo selfassembly to establish the nanoscopic materials.…”
Section: State Of the Art: Designs In Vivo Biodistribution And Petmentioning
confidence: 99%
“…The quantification of the impact of mPEG grafting density on the surface of organic polymer nanoparticles was made through a series of rigorous experimental studies (4). The key to the synthesis of the nanoparticles with well-defined and variable levels of mPEG surface grafts was the incorporation of the mPEGs onto the backbone of polymer building blocks that were designed to then undergo selfassembly to establish the nanoscopic materials.…”
Section: State Of the Art: Designs In Vivo Biodistribution And Petmentioning
confidence: 99%
“…Sun et al showed that block copolymers can be used to prepare nanomaterials for imaging (38). In this work, the metal chelator DOTA was grafted onto block copolymer precursors from which shell cross-linked knedellike nanoparticles were assembled.…”
Section: Hybrid Imaging Systemsmentioning
confidence: 99%
“…Paracellular permeability for peptides can be improved by using polymers such as chitosan [63], polyacrylates [64,82], and starch [78]. Chitosan is believed to Handbook 2015 improve paracellular transport of peptides such as insulin, due to its charge to bind to the epithelium, resulting in a structural reorganization of tight junction-associated proteins; polyacrylates act as absorption promoters, they are able to inactivate proteolytic enzymes from the intestinal lumen (e.g., trypsin) or those found in the brush border (aminopeptidases).…”
Section: Dependence Of Nanoparticle Size and Its Entry Into The Bodymentioning
confidence: 99%